2020
DOI: 10.4018/978-1-7998-2347-6.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility in the Agri-Food Sector

Abstract: Sustainable development is desired not only for public institutions but also for private companies that have realized the importance of sustainable management of limited resources available to mankind. The activity of large transnational corporations is not guided only by the principle of profit maximization, but also by corporate social responsibility (CSR). This chapter focuses on CSR programs run by agri-food companies taking into account the particularities of their activity and the importance of the consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…At the same time, new technologies impose the need for sectoral adaptation as part of either maintaining the competitiveness of the agricultural sector or reducing dependence on migrant labor in these areas. Also, as (Deblonde et al, 2007;Pandey et al, 2019;Borsellino et al, 2020;Jiang & Chen, 2020;Yao et al, 2020;Zaman et al, 2020) highlights the unsustainable or unethical practices of agri-food corporations such as inhumane treatment of livestock, use of pesticides and fertilizers with consequences on environmental and food contamination, genetically modified crops, water usage and recycling, questionable practices (such as misleading or double standard offers on product quality sold in developed and developing countries), environmental pollution, monopolistic practices, small farm exclusion, improper working conditions, land use change and land grabbing. Starting from the heterogeneous nature of agriculture, the implication effects of TNCs in the agri-food sector may be different, especially as the reaction of farmers is focused on ensuring the economic sustainability of their farms and less on CSR.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…At the same time, new technologies impose the need for sectoral adaptation as part of either maintaining the competitiveness of the agricultural sector or reducing dependence on migrant labor in these areas. Also, as (Deblonde et al, 2007;Pandey et al, 2019;Borsellino et al, 2020;Jiang & Chen, 2020;Yao et al, 2020;Zaman et al, 2020) highlights the unsustainable or unethical practices of agri-food corporations such as inhumane treatment of livestock, use of pesticides and fertilizers with consequences on environmental and food contamination, genetically modified crops, water usage and recycling, questionable practices (such as misleading or double standard offers on product quality sold in developed and developing countries), environmental pollution, monopolistic practices, small farm exclusion, improper working conditions, land use change and land grabbing. Starting from the heterogeneous nature of agriculture, the implication effects of TNCs in the agri-food sector may be different, especially as the reaction of farmers is focused on ensuring the economic sustainability of their farms and less on CSR.…”
Section: Introductionmentioning
confidence: 90%
“…In literature (Ene, 2009;Jan, 2009;Stancu, 2012) often globalization is considered as another factor that contributes to the remodeling of the agri-food sector, with positive contributions on food security but also negative effects such as standardization of dietary patterns that could influence health, segmentation, relocation of different stages of production, the existence of global chains that could affect trasability of food products, dependence of the agro-food sector on the distribution sector. As it is highlighted in (Jan, 2008, Aschemann-Witzel et al 2015Zaman et al, 2020), in developed countries, high living standards generate food waste, while in developing countries; much of the population is on the brink of poverty and lives in rural areas, where agriculture is a major source of livelihood. The increase in the demand for agri-food products has also favored the development of agro-industrial enterprises, a phenomenon observed mainly in developing countries.…”
Section: Transformation Of Agrifood Sector Under the Influence Of Formentioning
confidence: 99%
See 2 more Smart Citations
“…As remarked in the literature (Vasile & Ungureanu, 2014;Schwarz et al, 2015;Heijman et al, 2019;Bowers & Cheshire, 2019;Balogh & Jámbor, 2020), agriculture has to face new challenges imposed by the implementation of new production systems, climate change, price volatility, development of international trade with agricultural products, changing diets, urbanization or depopulation of rural areas At the same time, new technologies are imposed by the need for sectorial adaptation as part of either maintaining the competitiveness of the agricultural sector or reducing dependence on migrant labor in these areas. Also, as (Neumayer & De Soysa, 2005;Deblonde et al, 2007;Pandey et al, 2019;Borsellino et al, 2020;Jiang & Chen, 2020;Yao et al, 2020;Zaman et al, 2020) highlight the unsustainable or unethical practices of agri-food corporations such as inhumane treatment of livestock, use of pesticides and fertilizers with consequences on environmental and food contamination, genetically modified crops, water usage and recycling, questionable practices (such as misleading or double standard offers on product quality sold in developed and developing countries), environmental pollution, monopolistic practices, small farm exclusion, improper working conditions, exacerbation of child labour, land use change and land grabbing.…”
Section: Introductionmentioning
confidence: 99%